2014
DOI: 10.1093/hmg/ddu224
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants in FBN1 and FBN2 are associated with severe adolescent idiopathic scoliosis

Abstract: Adolescent idiopathic scoliosis (AIS) causes spinal deformity in 3% of children. Despite a strong genetic basis, few genes have been associated with AIS and the pathogenesis remains poorly understood. In a genome-wide rare variant burden analysis using exome sequence data, we identified fibrillin-1 (FBN1) as the most significantly associated gene with AIS. Based on these results, FBN1 and a related gene, fibrillin-2 (FBN2), were sequenced in a total of 852 AIS cases and 669 controls. In individuals of European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 77 publications
(70 reference statements)
6
91
1
3
Order By: Relevance
“…In addition, we could not find any putative functional variants in the LBX1 gene. In a recent exome sequencing study of a European population, rare variants in Fibrillin 1 and 2 were found to contribute to scoliosis [8]. We could not replicate these findings (data not shown).…”
Section: Discussioncontrasting
(Expert classified)
See 1 more Smart Citation
“…In addition, we could not find any putative functional variants in the LBX1 gene. In a recent exome sequencing study of a European population, rare variants in Fibrillin 1 and 2 were found to contribute to scoliosis [8]. We could not replicate these findings (data not shown).…”
Section: Discussioncontrasting
(Expert classified)
“…Recent genome-wide association studies have identified common genetic variants close to, or within, the ladybird homeobox 1 (LBX1), cell adhesion molecule L1-like (CHL1), and G protein-coupled receptor 126 (GPR126) genes, as well as an intergenic variant on 17q, in Asian and Caucasian populations [4][5][6][7]. One exome sequencing study has identified novel, rare variants associated with idiopathic scoliosis in the Fibrillin 1 and 2 genes in a European population [8]. However, these variants explain only a small part of the heritability of this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…They further sequenced exons of HSPG in 100 independent IS patients and found 21 other potentially damaging variants in HSPG . Buchan et al [48] exome-sequenced a cohort of 91 individuals with severe IS and compared the results with 337 controls. Using a gene burden analysis, they found that variants within the fibrillin 1 and 2 genes were associated with IS.…”
Section: Summary Of Genetic Findings In Idiopathic Scoliosismentioning
confidence: 99%
“…However, recent genetic studies have provided preliminary evidence that skeletal muscle dysfunction could be a contributory factor in AIS susceptibility: Firstly, rare variants in fibrillin-1 (FBN1) and fibrillin-2 (FBN2) have been found to be associated with severe AIS [6]. FBN1 and 2 are glycoproteins that form key components of skeletal muscle myofibrillar structure.…”
Section: Paraspinal Musclesmentioning
confidence: 99%